Villous adenoma of the bladder. Issue 5 (May 1993) - Channer, J L; Williams, J L; Henry, L
Abstract : A case of villous adenoma of the bladder associated with cystitis glandularis of intestinal type is described. Only three villous adenomas have been reported to date, of which two were also accompanied by cystitis glandularis. The lesion can be confused with polypoid hyperplasia in cystitis glandularis. Neutral mucins, acidic sulphomucins, and sialomucins were identified within the villous adenoma and adjacent areas of cystitis glandularis. It is suggested that the villous adenoma may form an intermediary stage in the development of some of the primary adenocarcinomas of the bladder arising in metaplastic intestinal mucosa.